Treatment of Hemangioma with High Dose Oral Corticosteroid - M. Sjabaroeddin Lubis; Zakaria Siregar; Nuraida Nuraida (Indonesian Pediatric Society, 1999)
A case with diagnosis of cavernous hemangioma in the hard palate wassuccessfully treated with 4-6 weeks of high dosage prednisone (2-3 mg/kgBW /day).Diagnosis of cavernous hemangioma was established based on physical examination.There was a mass in the hard palate, continuously bleeding and difficult to treat. After4-6 weeks treatment, the hemangioma regressed and never recurrent anymore.